Oxidation of Alcohols to Aldehydes and Ketones by HIO3 in Presence of NaHSO4·H2O - Khademian, Mohsen; Khademian, Maryam; Rahimnejad, Mostafa; Mokhtarian, Nader (Asian Journal of Chemistry, 2012)
Different types of alcohols are efficiently converted to their corresponding aldehyds and ketones with HIO3 in presence of NaHSO4·H2O. All reaction was performed in CH3CN medium in good to high yields.